2018
DOI: 10.1080/10715762.2018.1475733
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxidative stress in anxiety disorder: cause or consequence?

Abstract: Anxiety disorders are the most common mental illness in the USA affecting 18% of the population. The cause(s) of anxiety disorders is/are not completely clear, and research in the neurobiology of anxiety at the molecular level is still rather limited. Although mounting clinical and preclinical evidence now indicates that oxidative stress may be a major component of anxiety pathology, whether oxidative stress is the cause or consequence remains elusive. Studies conducted over the past few years suggest that anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(111 citation statements)
references
References 150 publications
(136 reference statements)
3
90
0
2
Order By: Relevance
“…From the evidence reviewed above, indicating a strong association between oxidative stress markers and anxiety-related behavior, the key question that arises is whether oxidative stress regulatory systems -particularly those engrained in the mitochondria-can modulate anxiety [72], and whether oxidative stress is a cause or a consequence of anxiety [73].…”
Section: Studies Targeting Genes Involved In Oxidative Stressmentioning
confidence: 99%
“…From the evidence reviewed above, indicating a strong association between oxidative stress markers and anxiety-related behavior, the key question that arises is whether oxidative stress regulatory systems -particularly those engrained in the mitochondria-can modulate anxiety [72], and whether oxidative stress is a cause or a consequence of anxiety [73].…”
Section: Studies Targeting Genes Involved In Oxidative Stressmentioning
confidence: 99%
“…Oxidative stress is another marker extensively investigated in psychiatric disorders, consisting of different mechanisms regulating the balance between reactive oxygen species (ROS) and antioxidant defenses [243]. Altered oxidative mechanisms may be responsible for the pathophysiology of psychiatric disorders as well and explain the overlap between ADs and other inflammatory-based diseases.…”
Section: Inflammation and Immune Systemmentioning
confidence: 99%
“…It has been suggested that oxidative stress (OS) plays a role in TMD and the experience of pain related to TMD 19,20 . It has also been proposed that increased OS may be associated with the pathogenesis of depression 21 and anxiety disorders 22 . Although OS has been implicated in the pathophysiology of many diseases due to the observed associations between OS and clinical symptoms 23 , whether OS is the cause or consequence of a disease (or perhaps both) remains elusive.…”
Section: Effect Of Occlusal Splint On Oxidative Stress Markers and Psmentioning
confidence: 99%